(untitled) (Annals of Medical Research, 2021)
Aim: To investigate the clinical features of open globe injuries treated in our clinic.Material and Methods: 65 eyes of 65 patients who were operated for open globe injury between 2016-2018 in Pamukkale University ophthalmology clinic were retrospectively analyzed. File records; age, sex, injury with which eye was affected, the cause and type of injury, biomicroscopic examination findings were recorded. The type of injury was classified as corneal, scleral and cornea-scleral according to localization.Results: 65 eyes of 65 patients were included in this retrospective study. 65 of 30 eyes were right eye and 35 eyes were left eye. The mean age of the patients was 41.33 ± 23.52 years. 15 (23.0%) of the patients were under the age of 18 and 50 (67%) were adults. 23 (35.4%) women and 42 (64.6%) men were included in the study. The causes of eye trauma are shown in Table 1. 35 (53.8%) of the injuries were classified as blunt and 30 (46.2%) were classified as penetrating injuries.Conclusion: Open globe injuries, which is one of the most important causes of preventable blindness, is an important public health problem, we think that necessary precautions should be taken and public awareness should be taken in this direction.